Delay differential equation of the 2nd order and it's an oscillation yardstick - Anmar Hashim Jasim (مجلة بغداد للعلوم, 2023)
This study focuses on studying an oscillation of a second-order delay differential equation. Start work, the equation is introduced here with adequate provisions. All the previous is braced by theorems and examplesthat interpret the applicability and the firmness of the acquired provisions